Latent tuberculosis infection in patients with chronic plaque psoriasis: evidence from the Italian Psocare Registry. (17th March 2015) - Gisondi, P.; Cazzaniga, S.; Chimenti, S.; Maccarone, M.; Picardo, M.; Girolomoni, G.; Naldi, L.; ,
Summary: Background: The nationwide prevalence of latent tuberculosis infection (LTBI) in Italian patients with psoriasis has never been investigated. Objectives: To estimate the nationwide prevalence of LTBI in Italian patients with psoriasis who are candidates for systemic treatment. Methods: Data were obtained from the Psocare Registry on those patients ( n  =   4946) with age > 18 years, systemic treatment at entry specified and tuberculin skin test (TST) performed according to the Mantoux method. LTBI diagnosis was based on a positive TST result in the absence of any clinical, radiological or microbiological evidence of active tuberculosis. Results: Latent tuberculosis infection was diagnosed in 8·3% of patients with psoriasis (409 of 4946). The prevalence of LTBI was lower in patients on biologics than in those on conventional systemic treatments, ranging from 4·3% (19 of 444) of patients on adalimumab to 31% (eight of 26) of those on psoralen–ultraviolet A ( P  <   0·05). Independent factors associated with LTBI were male sex [odds ratio (OR) 1·30, 95% confidence interval (CI) 1·04–1·62; P  =   0·02], age over 55 years (OR 2·93, 95% CI 2·18–3·93; P  <   0·001) and being entered into a conventional treatment (OR 3·83, 95% CI 3·10–4·74; P  <   0·001). Positive history of tuberculosis was seen in 1% of patients ( n  =   49). Conclusions: The nationwide prevalence of LTBI in Italian patients with psoriasis candidate to systemic treatment is high, and screening is recommended prior to biological treatment. Abstract : What's already known about this topic? Screening for latent tuberculosis infection (LTBI) is mandatory in patients with psoriasis candidate to biological therapy. The risk of developing active tuberculosis in patients treated with tumour necrosis factor‐α inhibitors is significantly higher than in subjects not exposed to biologics. What does this study add? The nationwide prevalence of LTBI in patients with psoriasis enrolled in the Psocare registry is 8·3%. Independent factors associated with LTBI were male sex, age over 55 years and being entered into a conventional treatment.